Cycling in Kindergarten: Highlighting Aspects of Integrating Cycling in Educational System (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
In this paper we examine the importance of including cycling in the educational system, starting at pre-school age. 74 children aged 4-5 years, 74 parents of 4-5 year olds and 4 preschool teachers participated in the study. We investigated the differences in the parents' and teachers' assessment of the children's cycling skills. We found that parents rated all observed cycling skills of their children better than preschool teachers (Wilcoxon signed ranks test: TS = 184.5 (74); p < 0.001). Children who find better conditions for cycling in their family environment are more skillful (Mann-Whitney test: U = 844.0 (74), p < 0.042), but the cycling skills of the children do not correlate with the cycling frequency of their parents (Spearman's rank correlation test: ro = -0.163 (74), p < 0.164). We conclude that it would be worthwhile to systematically introduce cycling both in preschool and in preschool teacher education.